2006
DOI: 10.1007/s00775-006-0157-y
|View full text |Cite
|
Sign up to set email alerts
|

More pronounced salt dependence and higher reactivity for platination of the hairpin r(CGCGUUGUUCGCG) compared with d(CGCGTTGTTCGCG)

Abstract: The DNA interference pathways exhibited by cisplatin and related anticancer active metal complexes have been extensively studied. Much less is known to what extent RNA interaction pathways may operate in parallel, and perhaps contribute to both antineoplastic activity and toxicity. The present study was designed with the aim of comparing the reactivity of two model systems comprising RNA and DNA hairpins, r(CGCGUUGUUCGCG) and d(CGCGTTGTTCGCG), towards a series of platinum(II) complexes. Three platinum complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 85 publications
2
30
0
2
Order By: Relevance
“…The application of polyelectrolyte theory to the platination of RNA or DNA suggests a model involving entry of a charged platinum species into the condensed cation atmosphere of a nucleic acid, followed by irreversible monoadduct and diadduct formation 12,5860. The range of literature values for the rate of monoadduct formation on duplex DNA by [Pt(NH 3 ) 2 Cl(OH 2 )] + varies from ~0.1 to 1 M −1 s −1 6163.…”
Section: Discussionmentioning
confidence: 99%
“…The application of polyelectrolyte theory to the platination of RNA or DNA suggests a model involving entry of a charged platinum species into the condensed cation atmosphere of a nucleic acid, followed by irreversible monoadduct and diadduct formation 12,5860. The range of literature values for the rate of monoadduct formation on duplex DNA by [Pt(NH 3 ) 2 Cl(OH 2 )] + varies from ~0.1 to 1 M −1 s −1 6163.…”
Section: Discussionmentioning
confidence: 99%
“…These results are complemented by in vitro studies describing RNA oligonucleotide targeting by cisplatin 1318 and by several Pt-drug conjugates. 19,20 In addition to these studies, our lab has recently reported that cisplatin is capable of crosslinking structurally complex RNAs.…”
Section: Introductionmentioning
confidence: 95%
“…19,20 In addition to these studies, our lab has recently reported that cisplatin is capable of crosslinking structurally complex RNAs. 21 Elmroth and coworkers 18 and our laboratory 21 have reported that in vitro , RNA binding is kinetically preferred over drug coordination to DNA. Taken together these initial findings raise important questions regarding which types of cellular RNAs may be targeted by cisplatin, and whether cellular RNA function is significantly impaired as a result.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that short RNAs may also represent good targets for cisplatin [77,78], and prompted further studies to better elucidate the basis of platinum-RNA interaction. Interestingly, in vitro studies performed using mono-aquated platinum complexes have shown that RNA platination kinetically competes or is even preferred over DNA platination [80,93]. Elmroth and co-workers investigated the interaction of cisplatin with the full length tRNA Ala and a short hairpin model (Mh Ala ) of its GC rich acceptor stem region ( Fig.…”
Section: Platinum Binding To Rnamentioning
confidence: 98%